Spirulina consumption effectively reduces anti-inflammatory and pain related infectious diseases. Issue 6 (November 2019) - Abu-Taweel, Gasem Mohammad; Mohsen G, Al-Mutary; Antonisamy, Paulrayer; Arokiyaraj, Selvaraj; Kim, Hak-Jae; Kim, Sun-Ju; Park, Kyeong Hun; Kim, Young Ock
Abstract: Background: Inflammation and pain triggers several pathological illnesses. Synthetic drugs used for the controlling of inflammatory conditions convey significant toxic effects. Global scientific community continually attempt to improve effective, economic and harmless naturally derived remedies against inflammation and pain. The present study aimed to quantify the phytochemical constituents of the freshly cultivated Spirulina and targeted to examining the anti-inflammatory and analgesic activity of Spirulina extract (SE) derived from Arthrospira platensis . Methods: The anti-inflammatory effect of SE was evaluated in animal models including carrageenan-induced rat hind paw oedema, and cotton pellet-induced granuloma formation. Analgesic effects of SE were evaluated by acetic acid induced writhing response and hot plate test. Results: Phytochemical quantification guided to identify seven carbohydrates, thirteen amino acids, eleven fatty acids and polyphenolic compounds respectively. The results indicated that SE significantly attenuated carrageenan-induced hind paw oedema, and cotton pellet-induced granuloma. Preliminary molecular mechanistic studies established that SE decreased the productions of TNF-α, IL-1β, IL-6, PGE2 and NO, and suppressed the activities of COX-2 and iNOS. Conclusion: These results provide a strong scientific foundation for the anti-inflammatory and analgesic activities of SE against different studies in animal models.